DETECTION OF Staphylococcus aureus BACTERIA ON ESCALATOR HANDRAINS IN GORONTALO SHOPPING CENTER - tahir, dheyiska; Dunggio, Yolan; Paramita, Diah Astini (Journal of Health, Technology and Science (JHTS), 2024)
Studies have shown that various types of bacteria can be found on escalator handrails, including Staphylococcus aureus . This bacteria can survive and reproduce on the surface of the escalator handrail, especially if environmental conditions allow, such as the right humidity and temperature. The purpose of this study was to determine the detection of bacteriaStaphylococcus aureus on escalator handrails .The method in this study uses a qualitative approach with a descriptive research type. This study was conducted using the scratch method or sample culture on Mannitol media. Salt Agar (MSA) and macroscopic , microscopic and catalase biochemical tests were carried out. The results of the study from 8 samples showed that 5 samples detected Staphylococcus aureus bacteria macroscopically showed round, irregular round, yellow, yellowish white and mucoid slimy colonies. Microscopic results showed round, grape-shaped, clustered and purple bacteria which were gram-positive bacteria.In the biochemical test (catalase test) gas bubbles were formed . While 3 samples did not detect Staphylococcus aureus bacteria by showing irregular colonies, yellowish white in color, microscopic results of rod-shaped bacteria (Bacillus), gram positive, in the Biochemical test (catalase) no air bubbles were formed.